Needs Analysis of Ngidang-Based Digital Storybooks for Moral Education in Children Aged 5–6 Years - Elfina Rahmawati; Sri Sumarni; Suratmi (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
This study aims to analyze teachers' needs for digital storybooks based on the local wisdom of the